Peran Ontologi dalam Teori Pendidikan Kontemporer - Ilahiya, Nabila Fadlla; Nugraha, Mulyawan Safwandy (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research explores the role of ontology as a philosophical foundation in shaping contemporary educational theory. Ontology, which focuses on the nature of reality and existence, has profound implications for teaching methods, curriculum design and evaluation of learning outcomes. This study highlights that ontological assumptions influence how knowledge is understood and implemented in educational contexts, especially in the complex digital age. Using a qualitative approach and desk research, this study reveals that ontology in education includes not only an understanding of physical reality but also the complex interactions between humans, technology and the environment. The results show that a more holistic, integrative and contextual ontological approach is needed to face today's educational challenges, such as character education and inclusion. In conclusion, critical reflection on the ontological assumptions underlying educational practices is essential for curriculum development that is more adaptive, relevant and responsive to global change.